2003
DOI: 10.1034/j.1600-0765.2003.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enamel matrix derivative on human periodontal fibroblasts: proliferation, morphology and root surface colonization. An in vitro study

Abstract: In conclusion, our data indicate that EMD enhances human PDL fibroblast proliferation. Furthermore, the cells in the presence of EMD show morphological changes that make them more similar to cementoblasts than to fibroblasts, suggesting a process of cellular differentiation that could play an important role in periodontal tissue repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
64
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 41 publications
(56 reference statements)
11
64
0
4
Order By: Relevance
“…EMD enhances the adhesion, proliferation and matrix production of fibroblast-like but not epithelial cells (Cattaneo et al, 2003;Gestrelius et al, 1997;Haase and Bartold, 2001;Hoang et al, 2000;Kawase et al, 2000). Attachment of human periodontal ligament cells to EMD is possibly mediated by bone sialoprotein as it can be inhibited by RGD-containing peptides or with an anti-avb3 integrin antibody (Suzuki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…EMD enhances the adhesion, proliferation and matrix production of fibroblast-like but not epithelial cells (Cattaneo et al, 2003;Gestrelius et al, 1997;Haase and Bartold, 2001;Hoang et al, 2000;Kawase et al, 2000). Attachment of human periodontal ligament cells to EMD is possibly mediated by bone sialoprotein as it can be inhibited by RGD-containing peptides or with an anti-avb3 integrin antibody (Suzuki et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of randomly selected tissues characterized the effects of treatments with GTR (5,10,19). Within the limits of our knowledge, the effects of EMP at the early stage (at 1, 2, and 4 weeks) of periodontal tissue healing have not been previously investigated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that EMD has no effect on ALP activity (59); however, EMD both decreases (57) and increases (62,73,74) ALP activity in PDL fibroblasts. The production of osteopontin and osteoprotegerin has been shown to be increased by EMD (60,74).…”
Section: Emdogain and Fibroblastsmentioning
confidence: 99%